Water intake of pigs consuming tiamulin during the nursery phase. Issue 1 (8th February 2021) - Vonnahme, Kimberly A; Mueller, Adam; Nelson, Daniel A; Vasquez-Hidalgo, Manuel Alexander; Amodie, Deborah; Short, Thomas H; Mellencamp, Martha A; Galina Pantoja, Lucina
Abstract: Mass medication to manage population health can be achieved by providing therapeutics in the drinking water. Young nursery pigs are highly sensitive to the flavor and smell of water. Medications that reduce water palatability often lead to an interruption in water and feed intake. With the availability of several generic water-soluble antimicrobials for pigs, questions have arisen about their palatability compared with the original product. In this study, we compared the intake of water containing tiamulin hydrogen fumarate from two different manufacturers with the intake of unmedicated water. The hypothesis was that the intake of tiamulin-containing water would be similar to unmedicated water. Water intake was monitored upon entry into the nursery and just prior to leaving the nursery. Also, average daily gain (ADG) and feed efficiency (FE) were determined. A total of 300 pigs were individually weighed (4.2–10.9 kg; avg = 6.8 kg) for randomization to pen ( n = 30 pens). The experiment had two time points: 1) early nursery (periods 1–3) and 2) late nursery (period 4). Pens were randomly assigned to a sequence (period 1–3) in a crossover experimental design containing three 10-d periods, with 5 d for the resetting of baseline where unmedicated water was provided followed by 5 d on tiamulin source addition [i.e., Triamulox TM (Zoetis, Parsippany, NJ); Denagard (Elanco Animal Health, Greenfield, IN)] or unmedicated water. After period 3 was concluded, all pens were given unmedicated water (via nipple waterers) and the number of pigs per pen was reduced to six pigs to maintain adequate space per pig. Ten days prior to pigs leaving the nursery, a fourth period was performed. After a 5-d water baseline was achieved, pens were treated with either unmedicated water or Triamulox- or Denagard-containing water. Pigs had ad libitum access to water and feed. During the testing periods, daily water intake was measured by a cup water system in each pen. Feed intake was measured every 5 d. There was no effect of treatment on initial body weights or weights at the beginning or end of each period ( P ≥ 0.51). Therefore, there was no effect of treatment on ADG ( P ≥ 0.23). Water intake ( P ≥ 0.16) and FE ( P ≥ 0.35) were not affected by treatment. Water consumption was similar among all treatments in each of the four periods. There appears to be no aversion to water intake when tiamulin hydrogen fumarate is added to the drinking water.